2023
DOI: 10.1002/ep.14164
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of mechanical, thermal, and acoustic performance of insulation materials containing microwave and ultrasound pretreated coffee wastes and estimation of thermal parameters using artificial neural network

Abstract: As a result of increasing coffee consumption in the world, the amount of coffee waste, which is an important environmental problem, is increasing. Due to their complex organic properties, they should not be discharged to landfills. At the same time, these wastes with a porous and cellulosic structure, have high acoustic and heat insulation performances in the building material they are used. In this study, commercial coffee wastes were evaluated without pre‐treatment (CW) and with microwave (MCW) and ultrasoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 28 publications
(62 reference statements)
0
4
0
Order By: Relevance
“…For non-structural elements, La Scalia et al [45] stated that the addition of coffee waste and fly ash in thermal mortars led to suitable values of mechanical properties. In another study with coffee residues, Yildiz et al [58] found that, in general, microwave and ultrasound pre-treated coffee waste additives improved the mechanical properties of mortars compared to raw coffee waste additives. The authors also highlight that pretreatment of raw coffee waste led to an increase in 10% in compressive strength.…”
Section: Mechanical Resistancementioning
confidence: 99%
See 3 more Smart Citations
“…For non-structural elements, La Scalia et al [45] stated that the addition of coffee waste and fly ash in thermal mortars led to suitable values of mechanical properties. In another study with coffee residues, Yildiz et al [58] found that, in general, microwave and ultrasound pre-treated coffee waste additives improved the mechanical properties of mortars compared to raw coffee waste additives. The authors also highlight that pretreatment of raw coffee waste led to an increase in 10% in compressive strength.…”
Section: Mechanical Resistancementioning
confidence: 99%
“…Vegetal wastes: coffee waste a,b (3), cork waste a (3), fallen leaves fibres a,b (3), hemp shives a,c (2), rice husk ash a,b (2), wood waste a,b (2), bagasse ash b (1), desiccated and smashed desiccated platanus acerifolia fruits a (1), chopped cane stalks a (1), almond/hazelnut/nut shells a (1), coconut shells a (1), bean and pea pods a (1), curauá fibres e (1), sunflower plant bark and pith a (1), recycled jute fibre c (1), thistle fibre c (1), olive stone e (1) [16,28,35,36,40,45,[57][58][59][60][61][62][63][64][65][66] 3 Animal waste: ground waste seashells b (1) [67] 4…”
Section: Item Wastesmentioning
confidence: 99%
See 2 more Smart Citations